1991
DOI: 10.1128/aem.57.4.1094-1101.1991
|View full text |Cite
|
Sign up to set email alerts
|

Modeling of bacterial growth as a function of temperature

Abstract: The temperature of chilled foods is a very important variable for microbial safety in a production and distribution chain. To predict the number of organisms as a function of temperature and time, it is essential to model the lag time, specific growth rate, and asymptote (growth yield) as a function of temperature. The objective of this research was to determine the suitability and usefulness of different models, either available from the literature or newly developed. The models were compared by using an F te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
171
0
15

Year Published

1997
1997
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 387 publications
(203 citation statements)
references
References 14 publications
3
171
0
15
Order By: Relevance
“…In contrast, broad temperature ranges (often spanning > 40°C) have been explored in studies of substrate-limited microbial growth in batch cultures and commercial food products (e.g. Zwietering et al 1991;Zanoni et al 1993;Singh et al 2011;Urit et al 2013). These studies found unimodal temperature dependence of the intrinsic growth rate, while carrying capacity changed either slightly (and unimodally) with temperature or not at all before abruptly collapsing at high temperatures, similar to the pattern predicted for the closed, nutrient-limited system.…”
Section: Temperature Dependence Of Prey Carrying Capacitymentioning
confidence: 96%
“…In contrast, broad temperature ranges (often spanning > 40°C) have been explored in studies of substrate-limited microbial growth in batch cultures and commercial food products (e.g. Zwietering et al 1991;Zanoni et al 1993;Singh et al 2011;Urit et al 2013). These studies found unimodal temperature dependence of the intrinsic growth rate, while carrying capacity changed either slightly (and unimodally) with temperature or not at all before abruptly collapsing at high temperatures, similar to the pattern predicted for the closed, nutrient-limited system.…”
Section: Temperature Dependence Of Prey Carrying Capacitymentioning
confidence: 96%
“…2). High temperatures have often been reported to increase the maximum cell density in microbial growth modelling (Zwietering et al 1991;Koseki & Isobe 2005) but not always (Baranyi & Pin 2001;Kim et al 2003). Product characteristics and the specific microbial organisms concerned determine the dynamics of the maximum attainable growth level.…”
Section: Resultsmentioning
confidence: 99%
“…Cook-chill or sous vide products preserved with mild heating in a central kitchen are also often limited in their shelf life due to microbial spoilage in foodservice facilities (Church 1998). Many ready-to-eat foods are prepared by mild braising of the ingredients and/or pasteurisation and are susceptible to microbial proliferation, even though the salting, cooking and heating steps provide some degree of preservation (Zwietering et al 1991;Gould 1996;Kim et al 2003;Galimpin-Johan et al 2007). Although there have been some technological developments in preserving these prepared products, the precise determination of their storage life is required to ensure their quality and safety in the foodservice environment.…”
Section: Introductionmentioning
confidence: 99%
“…Results are shown in Table 4. In order to model bacterial growth as a function of temperature, there are several models available in the scientific literature (Hinshelwood, 1946;Ratkowsky et al, 1982;Zwietering et al, 1991;Baranyi et al, 1993;Rosso et al, 1993;Whiting et al, 2000). They are based on either a mechanistic or empirical approach.…”
Section: Effect Of Temperature and Time On The Growth Of Salmonella Imentioning
confidence: 99%